Patrones de distribucion espacial en plantas clonales - Carrillo Angeles, I.G.=700 1 Mandujano, M. del C.
(Es, En)
Ilus., 102 ref.
Keywords: CLONES; CRECIMIENTO; DISTRIBUCION GEOGRAFICA; BIODIVERSIDAD; HIBRIDACION; MEXICO; PLANTAS CLONALES; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO